Effect of vitrification on spermatozoa quality in bull semen - Lee, Lian Yu (2017)
Cryopreservation of spermatozoa is part of the assisted reproductive biotechnology to enhance reproductive capacity in livestock. Conventional cryopreservation applies slow-gradual freezing method permitted ice crystallization and causes cryodamage resulting in poor post-thawed semen quality. Hence, vitrification is introduced by solidifying the solution into glassy state without causing any crystallization in fast and inexpensive manner. This ultra-rapid cooling method requires high concentration of cryoprotectants that potentially toxic the spermatozoa. Therefore, this study was conducted to determine the effect of vitrification on the quality of bull semen. A total of eight (8) bull semen samples were collected using electro-ejaculation. Tris-based extender was compared with vitrification using solution of different concentration of cryoprotectants at 10% (Vitrification Solution 1; VS-1) and 20% (VS-2) containing dimethyl sulfoxide (DMSO) and ethylene glycol respectively. The result revealed that high mortality and nearly zero motility in all post-warmed vitrified spermatozoa, but the general and progressive motilities parameters in VS-1 at initial evaluation was 22.45% and 24.87% respectively better than Tris-based extender and was statistically significant. In conclusion, vitrification has potential as an alternative for cryopreservation. Therefore, further research on spermatozoa vitrification technique on enhancement in cooling and warming should be conducted and investigated.